2021
DOI: 10.2478/rjr-2021-0008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, morbidity and mortality of deep neck abscess in a tertiary hospital from Northwestern Mexico

Abstract: BACKGROUND. Neck abscesses are defined as processes of infectious origin, which form a collection of purulent material through the deep planes of the neck, formed by fasciae. It may involve one or more spaces of the cervical region. In addition, they can be localized or disseminated and generate extremely serious and life-threatening complications.OBJECTIVE. To identify the prevalence of deep neck abscess in our tertiary hospital center.MATERIAL AND METHODS. A retrospective, analytical, observational, and cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The morbidity rate was approximately 9.9% with the presence of neck contracture, restricted mouth opening, and reoccurred DNA. 11 Furthermore Pineda-Alvarado et al, 12 reported that there is an 8.33% mortality rate among 36 total patients and 13.88% of them were admitted to the intensive care unit. On the other hand, the costs of DNA management were particularly scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The morbidity rate was approximately 9.9% with the presence of neck contracture, restricted mouth opening, and reoccurred DNA. 11 Furthermore Pineda-Alvarado et al, 12 reported that there is an 8.33% mortality rate among 36 total patients and 13.88% of them were admitted to the intensive care unit. On the other hand, the costs of DNA management were particularly scarce.…”
Section: Introductionmentioning
confidence: 99%
“…DNSI is not common in the general population with an estimated 0.01% incidence within the United States, but there is not a nationwide prevalence study. 1 The mortality of DNSI is not thoroughly studied and seems to vary widely, with reports ranging from 1% to 8%. 1,2,5,6 A nationwide, retrospective study on DNSI in patients with ESRD in Taiwan identified ESRD as a risk factor for DNSI, concluding that ESRD conferred twice the risk of developing DNSI compared to patients without ESRD.…”
Section: Introductionmentioning
confidence: 99%
“…Deep neck space infections (DNSI) are potentially fatal infections that reside within the deep spaces of the cervical neck fascia. 1 They are most often caused by odontogenic infections but they can also be caused by trauma, neighboring infections of the salivary glands or tonsils, dental procedures, or malignancies. 2 Treatment delays can lead to complications such as compromised airways, mediastinitis, meningitis, pneumonia, and jugular vein thrombosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation